[Boxing ; Basil Valdez ; STL [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Deals with controversy of two Filipino boxers in a face-off to determine who will represent the country in the Seoul Olympics; the evils and benefits of small town lottery in the Philippines; and the interviews with top Filipinos balladeer about his philosophy in life.